2003
DOI: 10.1002/car.821
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of instruments designed to predict child maltreatment during the antenatal and postnatal periods

Abstract: The purpose of this review was to identify instruments designed to predict future child maltreatment and to evaluate their predictive accuracy. A number of electronic databases were searched to identify published studies. Only studies that had utilized a prospective methodology and tested at least one standardized instrument designed to identify families during the antenatal or postnatal periods who are at increased risk of maltreatment were included in the review. Eight studies were included that had prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 15 publications
(150 reference statements)
1
25
0
Order By: Relevance
“…Seventeen citations were selected, and five key reviews retained as evidence. [443][444][445][446][447] Studies conducted with general population and ethnic minority samples provided additional evidence that informed our recommendations related to child maltreatment among immigrants and refugees.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen citations were selected, and five key reviews retained as evidence. [443][444][445][446][447] Studies conducted with general population and ethnic minority samples provided additional evidence that informed our recommendations related to child maltreatment among immigrants and refugees.…”
Section: Resultsmentioning
confidence: 99%
“…443,445 All screening methods attempt to predict child maltreatment on the basis of either parents' potential for maltreatment or the presence or level of risk factors associated with maltreatment, rather than on the occurrence of actual maltreatment. Three systematic reviews have reported that these instruments tend to have high sensitivity but poor specificity and false-positive rates too high for use in clinical settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In predicting risk of child abuse and neglect, existing risk instruments lead to an unacceptably high level of false positives (families inaccurately deemed to be high risk) and high level of false negatives (dangerous families wrongly judged safe) (Munro, 2004;Peters and Barlow, 2003). With respect to predicting criminality and social exclusion, the reports are mixed:…”
Section: Evaluating a Screening Programmementioning
confidence: 99%
“…5 The importance of targeted interventions at an early stage of pregnancy should not be underestimated. [6][7][8] learning and willing to stop negative behaviour that affects their unborn child. 9 To be able to do so, these high risk young women need someone to inform and empower them to stop negative behaviour and to encourage attachment with their child.…”
Section: Introductionmentioning
confidence: 99%